Epidemiologi, Patotipe, dan Strategi Pengendalian Penyakit Hawar Daun Bakteri pada Tanaman Padi - Sudir Sudir; B. Nuryanto; Triny S. Kadir (Iptek Tanaman Pangan, 2012)
Bacterial leaf blight (BLB) in rice is an important disease on rice in rice-producing countries, including in Indonesia. The disease is caused by the bacterium of Xanthomonas oryzae pv. oryzae (Xoo). Pathogen infected leaf of rice plants in all plant growth stages, from nursery to harvest. Symptom on the vegetative phase of plant is called kresek and that at the generative phase is called as blight. When the attack occurred in the generative phase, grain filling process was halted, resulting in less than perfect kernels. Yield losses due to the bacterial blight disease varied between 15 to 80%, depending on the crop stadia when the diseases occurred. BLB disease development is strongly influenced by environmental factors, especially moisture, temperature, method of cultivation, varieties and rate of nitrogen fertilization. It is therefore recommended that BLB control is integrated with other methods that would suppress the progress of the disease. Resistant varieties are considered as a key component in an integrated disease control of BLB. But this technology is hampered by the ability of the pathogen to adapt and to form new pathotipes which are more virulent, so that varietal resistance is easily broken. BLB disease control by planting resistant varieties must be adapted to the existing pathotipe. Monitoring and mapping the composition and distribution of bacterial Xoo pathotipe are indispensable as basic recommendation of BLB control. Planting resistant varieties according to the presence pathotipe occurrence could minimize the disease severity.